Body appearance (Dis)satisfaction scale applied to Brazilian university students - Martins, Bianca Gonzalez [UNESP]; Barra, Júlia Valério [UNESP]; da Silva, Wanderson Roberto [UNESP]; Marôco, João; Campos, Juliana Alvares Duarte Bonini [UNESP] (FapUNIFESP (SciELO), 2021)
Objective: This study aimed to estimate the psychometric properties of the Body Area Scale (BAS) applied to a sample of Brazilian university students to support the validity and reliability of the obtained data. Methods: We performed confirmatory factor analysis (CFA) using the Comparative Fit index (CFI), Tucker-Lewis index (TLI), and Root Mean Square Error of Approximation (RMSEA). We calculated the average variance extracted (AVE), composite reliability (CR), and ordinal alpha coefficient (α). All estimates were calculated separately for women and men. A thousand students participated (women = 64.0%, mean [M] age = 20.92, standard deviation [SD] = 2.40 years; body mass index (BMI) M = 23.24, SD = 3.97 kg/m2). Results: Considering the CFA results, the original unifactorial model (24 items) did not fit data for women and men. Instead, the two-factorial model with 19 items had adequate fit for male and female samples (CFI = 0.922-0.958; TLI = 0.912-0.952; RMSEA = 0.090-0.096), as well as good convergent validity (AVE = 0.536-0.668) and reliability (CR = 0.920-0.952; α = 0.916-0.948). Once BAS was proposed to evaluate satisfaction/dissatisfaction with one’s own body, and considering the reformulation of the factorial model, we proposed a new name for the instrument: Body Appearance (Dis)Satisfaction Scale (BAS-R). Conclusion: Professionals can now include the BAS-R in future protocols to evaluate satisfaction/dissatisfaction with the body in Brazilian students.
Escala de (In)Satisfação com a Aparência Corporal aplicada a universitários Brasileiros
Keywords: Body image; Dissatisfaction; Factorial analysis; Satisfaction; Students